Descriptive analysis of national bovine viral diarrhoea test data in England (2016–2020). (25th July 2022) - Prosser, Naomi S.; Hill, Edward M.; Armstrong, Derek; Gow, Lorna; Tildesley, Michael J.; Keeling, Matt J.; Kaler, Jasmeet; Ferguson, Eamonn; Green, Martin J.
Abstract: Background: Bovine viral diarrhoea virus (BVDV) causes substantial economic losses to the cattle industry; however, control and eradication can be achieved by identifying and removing persistently infected cattle from the herd. Each UK nation has separate control programmes. The English scheme, BVDFree, started in 2016 and is voluntary. Methods: We analysed the test results submitted to BVDFree from 5847 herds between 2016 and 2020. Results: In 2020, 13.5% of beef breeders and 20.0% of dairy herds that submitted tests had at least one positive (virus/antibody) test result. Although lower than in previous years, there was no clear trend in the proportion of positive tests over time. In virus testing herds, 0.4% of individual tests were positive in 2020, and 1.5% of individual tests were positive in BVDV‐positive virus testing herds. Dairy herds and larger herds were more likely to join BVDFree, and dairy herds were also more likely to virus test than beef breeder herds. Larger herds, herds that used virus testing and herds that had BVDV‐positive test results were more likely to continue submitting tests to BVDFree. Conclusions: The findings provide a benchmark for the status of BVDV control in England; continued analysis of test results will be important to assess progress towards eradication.